Comparative analysis of the remineralization potential of different active ingredients based toothpastes using SEM/EDX: An in vitro study - Kukey Pelin; Turkmen Cafer; Cimilli Zuhre Hale (Balkan Stomatological Society, 2024)
Background/Aim: The principal purpose of this study was to investigate the efficacy of different active ingredients to inhibit demineralization around the margins of cervical cavities in natural teeth by scanning electron microscopy and energy dispersive X-Ray elemantal analysis (SEM-EDX). Material and Methods: Thirty-two sound human molars were used. Box-shaped cavities were prepared along the cemento enamel junction (CEJ). The samples were were immersed in a demineralization solution (pH=1) maintained for 72 hours and randomly divided into 4 groups. Surfaces according to the groups were treated with potassium nitrate, arginine and calciumsodiumphosphosilicate containing remineralization agents for 14 days, respectively and the samples in control group were submitted to toothbrushing with deionized water. The samples were analyzed by using SEM-EDX analysis. Data was statistically analyzed using by one way ANOVA (analysis of variance) test and LSD (least significant difference) test for comparison between means at a significance level of 0.05. Results: SEM-EDX elemental mapping was used to evaluate the degradation from depth profiles of fluoride (F), Calcium (Ca), and phosphate (P) leaching. Micromorphological and elemental analyses were done using SEM and EDX. SEM EDX Analysis on enamel showed a significant difference between the groups except the control group (p<0.05). The dentine results showed significant differences between the control group and all other groups (p<0.05). Elemental analysis showed significant differences in Ca weight percentage among the first and second observation levels in all groups (p<0.05). Conclusions: In conclusion, all tested toothpastes showed some ability to resist demineralization at the margins. The groups except control group showed better outcomes compared with the other tested samples.